Systematic Review and Meta-analysis of Diagnostic Accuracy of Percutaneous Renal Tumour Biopsy - Marconi, Lorenzo; Dabestani, Saeed; Lam, Thomas B; Hofmann, Fabian; Stewart, Fiona; Norrie, John; Bex, Axel; Bensalah, Karim; Canfield, Steven E; Hora, Milan; Kuczyk, Markus A; Merseburger, Axel S; et al. (European urology, 2016)
CONTEXT: The role of percutaneous renal tumour biopsy (RTB) remains controversial due to uncertainties regarding its diagnostic accuracy and safety. OBJECTIVE: We performed a systematic review and meta-analysis to determine the safety and accuracy of percutaneous RTB for the diagnosis of malignancy, histologic tumour subtype, and grade. EVIDENCE ACQUISITION: Medline, Embase, and Cochrane Library were searched for studies providing data on diagnostic accuracy and complications of percutaneous core biopsy (CB) or fine-needle aspiration (FNA) of renal tumours. A meta-analysis was performed to obtain pooled estimates of sensitivity and specificity for diagnosis of malignancy. The Cohen kappa coefficient (κ) was estimated for the analysis of histotype/grade concordance between diagnosis on RTB and surgical specimen. Risk of bias assessment was performed (QUADAS-2). EVIDENCE SYNTHESIS: A total of 57 studies recruiting 5228 patients were included. The overall median diagnostic rate of RTB was 92%. The sensitivity and specificity of diagnostic CBs and FNAs were 99.1% and 99.7%, and 93.2% and 89.8%, respectively. A good (κ = 0.683) and a fair (κ = 0.34) agreement were observed between histologic subtype and Fuhrman grade on RTB and surgical specimen, respectively. A very low rate of Clavien ≥ 2 complications was reported. Study limitations included selection and differential-verification bias. CONCLUSIONS: RTB is safe and has a high diagnostic yield in experienced centres. Both CB and FNA have good accuracy for the diagnosis of malignancy and histologic subtype, with better performance for CB. The accuracy for Fuhrman grade is fair. Overall, the quality of the evidence was moderate. Prospective cohort studies recruiting consecutive patients and using homogeneous reference standards are required. PATIENT SUMMARY: We systematically reviewed the literature to assess the safety and diagnostic performance of renal tumour biopsy (RTB). The results suggest that RTB has good accuracy in diagnosing renal cancer and its subtypes, and it appears to be safe. However, the quality of evidence was moderate, and better quality studies are required to provide a more definitive answer.
Keywords: nádory ledvin; Renal cell carcinoma; Humans; biopsie dutou jehlou; Diagnosis; Predictive Value of Tests; Meta-analysis; lidé; Renal mass; reprodukovatelnost výsledků; Fine-needle aspiration; Neoplasm Grading; Reproducibility of Results; prediktivní hodnota testů; stupeň nádoru; Accuracy; karcinom z renálních buněk; Biopsy, Fine-Needle; Carcinoma, Renal Cell; odchylka pozorovatele; Observer Variation; tenkojehlová biopsie; Kidney Neoplasms; Biopsy, Large-Core Needle; Needle core biopsy